Estimation Parameters and Evaluation of Cropsyst Model to Predict the Growth and Yield of Two Wheat Cultivars in Northeast Khuzestan - JAFAR POURREZA; Sayed yaghoub hashemi; abdolah bahrani; mehran mombaini (رویکردهای نوین در مهندسی آب و محیط زیست)
To Estimate Parameters and Evaluation of Cropsyst Model to Predict the Growth and Yield of Two Wheat Cultivars in Northeast Khuzestan, an field experiment was conducted in the form of randomized complete block design in a research farm in Ramhormoz with three replications. Factors were included irrigation regime at two levels (full irrigation and stop irrigation after flowering), cultivation date (six dates including: October 30, November 15, November 30, December 15, December 30, and January 15) and two varieties of wheat. (Chamran 2 and Sirvan). Based on the results, the critical day length, the ceiling day length, the number of basic vernalization days, the minimum growth rate in the absence of vernalization, and the saturation point of vernalization for Chamran 2 variety are equal to 14, 8, zero, and 0.9, respectively. and 24, and for the number of Sirvan, it was 13.8, 7.8, zero, 0.93 and 25, respectively. The results obtained from the simulation of flowering and physiological ripening stages based on RMSE, d, CRM and EF statistics showed that the Cropsyst model simulated the mentioned stages with good accuracy for different figures. The simulation results of dry matter of aerial organs for different figures showed that this model was able to simulate 95 to 98 percent of this parameter in different treatments of planting date and irrigation. The error value of the model based on the RMSE statistic for the dry matter of aerial organs in Chamran 2 and Sirvan cultivars was 627 and 351 kg per hectare, respectively.